Sensory Deafness in Workers at PT X Rokan Hulu Palm Oil Mill - Hidayatul Fitri (International Journal of Public Health, 2024)
Sensorineural deafness is a type of hearing loss that commonly occurs due to noise exposure in the workplace, including in palm oil mills (PKS). This condition can reduce the quality of life of workers and have an impact on productivity. This study aims to identify the prevalence and factors that influence the occurrence of sensorineural deafness in palm oil mill workers, with a focus on the Pekanbaru area. This research method uses observational research, measuring deafness using a tuning fork. at PT X in July 2020. Results. From the analysis univariate It was found that 58.6% of PKS workers experienced sensorineural deafness. The conclusion is that more than half of the workers experiencing sensorineural deafness .